KINETIC STUDY AND BASAL MEDIA MODIFICATION OF CELLULASE ENZYME PRODUCTION BY MUTATED STRAIN OF ASPERGILLULS FUMIGATES (AF1) - DR. AMAL ALOTAIBI; DR. JOHRA KHAN (International Journal of Pharma and Bio Sciences, 2016)
Kine and colchicine t tic parameters play important role in microbial cellulase production. After mutation with UV irradiation he highest cellulase producing Aspergilluls fumigates (Af1) stain is used to study the effect of culture conditions. It was found that Lactose 1%(W/V) was best carbon source, Carboxy methyl cellulose (CMC) 3% (W/V) as the best substrate concentration, pH 6 is found to be best suitable pH for high cellulase production. Peptone served as best nitrogen source at 350C significant increase in cellulase production was observed. In compression to wild strain 30 to 90% increase in cellulase production concluding Aspergilluls fumigates (Af1) as a better source of cellulase enzyme.